Surgical management of ventrally located cervical epidural abscess: a comparative analysis between patients aged 18-64 years and ≥65 years - Lenga, Pavlina; Gülec, Gelo; Kiening, Karl; Unterberg, Andreas; Ishak, Basem (World neurosurgery: X, 2024)
Background - We aimed to compare the clinical course of patients aged 18-65 years and ≥65years who underwent anterior cervical discectomy and fusion (ACDF) or corpectomy for ventrally located CSEA. - Methods - Clinical and imaging data were retrospectively collected from the institutional database between September 2005 and December 2021. - Results - A total of 35 and 26 patients aged 18-64 and ≥ 65 years, respectively who were diagnosed with ventrally located CSEA were included. The overall mean age was 63.9 ± 3.2 years, with a predominance of the male sex (n = 43/61, 70.5%). Patients aged ≥65 years presented with significantly higher rates of comorbidities (10.3 ± 2.8), as indicated by the CCI, than their younger counterparts (18-64 years: 6.2 ± 2.6; p < 0.001). No differences in the surgical approach or characteristics were observed among the groups. Notably, patients aged ≥65 years had a significantly longer intensive care unit as well as overall hospital stay. In-hospital and 90-day mortality were similar across both groups. Following both types of surgery, a significant improvement was observed in the blood infection parameters and neurological status at discharge compared with the baseline measurements. Older age, higher rates of comorbidities, and higher grades of disability were significant predictors for mortality. - Conclusions - Emergency surgical evacuation should be undertaken for CSEA in the presence of acute neurological deterioration regardless of the age. Factors, such as age, comorbidities, and neurological status on admission appear to be important predictors of disease outcomes. However, the risk profile of younger patients should not be underestimated.
Gesehen am 21.05.2025